Test-training integration to optimize performance and health in baseball pitchers: An outcome-driven approach - Morrison, G.; Ashworth, B.; Read, P. J. (Strength and Conditioning Journal, 2024)
Upper-limb injuries are common among baseball pitchers, creating significant time loss for the player and financial loss for the team. Multiple studies have outlined the kinetics and kinematics of a baseball pitch, and many of which evaluate testing or training methods to enhance performance and reduce injury risk. However, a systematic approach that integrates testing and training to optimize health and performance in baseball pitchers has not been presented. The aims of this article are threefold: (a) analyze the sport demands to identify the key biomechanical requirements and injury epidemiology; (b) present a test battery to examine the components identified in the needs analysis; and (c) develop a progressive sequence of exercises related to each of the assessments performed, which can then be used to formulate an athletic training program.